Non-coding RNAs regulate autophagy process via influencing the expression of associated protein. (March 2020) - Zhao, Yunyi; Wang, Ze; Zhang, Wenhui; Zhang, Linbo
Abstract: Autophagy is a tightly-regulated multi-step process involving the lysosomal degradation of proteins and cytoplasmic organelles. Central to this process is the formation of the autophagosome, a double membrane-bound vesicle, which is fuse with lysosomes or endosomes, and then deliver its cytoplasmic cargo to the lysosomes. Here, we summarize the recent process of autophagy, focusing on protein molecules, their complexes, and its essential roles of autophagy in various phases. Emerging evidence has revealed that miRNAs, lncRNAs, and circRNAs play an indispensable role in autophagy regulation by modulating targeting gene expression. This review we will summarize the main features of ncRNAs and point to gaps in our current knowledge of the connection between ncRNAs and autophagy, as well as their potential utilization in various disease phenotypes. Also, we highlight recent advances in ncRNAs and autophagy-associated protein interaction and how they regulate the autophagy process.